The Influence of Profit Pressure, Earning Management, and Good Corporate Governance on Fraudulent Financial Reports - Muhammad Nur Salim; Aspahani Aspahani; Hasni Yusrianti (Jurnal Ekuilnomi, 2025)
This study aims to analyze the effect of Profit Pressure, Earning Management, and Good Corporate Governance on Fraudulent Financial Reporting (FFR) in transportation companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The sample consists of 34 companies selected using purposive sampling, and the data were analyzed using panel data regression with the Common Effect Model (CEM). The results indicate that Profit Pressure and Earning Management have no significant effect on Fraudulent Financial Reporting. However, Good Corporate Governance has a significantly positive effect in reducing FFR, although some indicators, such as the frequency of audit committee meetings, show no significant impact. This study highlights the importance of implementing good corporate governance principles to prevent financial statement manipulation and enhance reporting integrity